STUDI PERTUMBUHAN BEBERAPA ISOLAT JAMUR TIRAM (Pleurotus spp.) PADA BERBAGAI MEDIA BERLIGNIN - Achmad ;; Elis Nina Herliyana; Wartaka ; (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
The Growth Study of Some Oyster Mushroom (Pleurotus spp.) Isolates on Some Ligneous Media. Research to study the growth of some pleurotus isolates on some ligneous media were conducted at Forest Pathology Laboratory, Faculty of Forestry and Biological Science Study Center, Bogor Agricultural University in September 2004 to March 2005. Substances which used were Pleurotus sp.l, Pleurotus sp.6, and Pleurotus sp.8 from Forest Pathology laboratory collection, PDA, MEA, MPA, some natural lignin source to be added to the commercial media. Optimum media for Pleurotus sp.1 is PDA, MEA + bamboo apus dust, and Glenn and Gold modification + sengon wood dust. Pleurotus sp.6 grow best at MPA, MEA + paddy straw dust, and Glenn and Gold modification + paddy straw dust. Optimum media for Pleurotus sp.8 is MPA, MBA + paddy straw dust added media, MEA + paddy hay dust, and Glenn and Gold modification + sengon wood dust. The difference of colony growth is caused by isolate and nutrition of each growth media. Pleurotus sp.6 and Pleurotus sp.8 known produce lyses zone at media which contain lignin source. Lyses zone caused by existence of extrasellular enzyme which secreted by mushroom hype to degrade lignin. All mycellium dry weight of Pleurotus spp. isolat that is given wobble is higher than don't given. Mycellium dry weight from high to low showed by Pleurotus sp.8, Pleurotus sp.6 and Pleurotus sp.l. The difference of colony growth caused by isolat and nutrition of each growth media. Lysis zone at media with lignin source caused by extracellular enzyme activity to degradate lignin source as their nutrition. The difference of mycellium dry weight at both treatment is caused by the response to oxygen in the liquid media. Key words: Pleurotus spp, PDA, MEA, MPA, bamboo dust, sengon wood dust, Glenn & Gold, modification. Penelitian ini bertujuan untuk mempelajari pertumbuhan koloni beberapa isolat jamur tiram (Pleurotus spp.) yang dikulturkan pada berbagai media dengan sumber lignin alami, dilakukan dan bulan September 2004 sampai Maret 2005, bertempat di Laboratorium Penyakit Hutan, Fakultas Kehutanan, dan Laboratorium Mikrobiologi dan Biokimia, Pusat Studi Ilmu Hayat, Institut Pertanian Bogor. Bahan yang digunakan adalah Pleurotus sp.1, Pleurotus sp.6, dan Pleurotus sp.8, MEA, MPA, PDA, dan beberapa macam sumber lignin alami yang ditambahkan pada tiga media komersial tersebut. Pleurotus sp.l tumbuh terbaik pada media PDA, MEA + serbuk kayu sengon, serta media modifikasi Glenn dan Gold + serbuk bambu apus. Pleurotus sp.6 tumbuh terbaik pada media MPA, MEA + serbuk jerami padi, serta media modifikasi Glenn dan Gold + serbuk jerami padi. Isolat Pleurotus sp.8 tumbuh terbaik pada media MPA, MEA + serbuk kayu sengon, serta media modifikasi Glenn dan Gold + serbuk jerami padi. Pleurotus sp.6 dan Pleurotus sp.8 menghasilkan zona lisis berbentuk lingkaran coklat kekuningan pada media yang ditambah sumber lignin alami. Bobot kering miselia Pleurotus spp. pada media malt ekstrak cair yang ditambah serbuk jerami padi atau serbuk kayu sengon dengan diberi penggoyangan, lebih tinggi dibanding dengan Pleurotus spp. pada media yang sama tanpa diberi penggoyangan. Bobot kering miselia tertinggi sampai terendah berturut-turut ditunjukkan oleh Pleurotus sp.8, Pleurotus sp.6, dan Pleurotus sp.1 . Kata kunci: Pleurotus spp, PDA, MEA, MPA, serbuk bambu, serbuk kayu sengon, modifikasi Glenn dan Gold